2015
DOI: 10.2147/ijn.s76062
|View full text |Cite
|
Sign up to set email alerts
|

Differential nanoreprotoxicity of silver nanoparticles in male somatic cells and spermatogonial stem cells

Abstract: Background Silver nanoparticles (AgNPs) possess unique physical, chemical, and biological properties. AgNPs have been increasingly used as anticancer, antiangiogenic, and antibacterial agents for the treatment of bacterial infections in open wounds as well as in ointments, bandages, and wound dressings. The present study aimed to investigate the effects of two different sizes of AgNPs (10 nm and 20 nm) in male somatic Leydig (TM3) and Sertoli (TM4) cells and spermatogonial stem cells (SSCs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 115 publications
3
28
0
Order By: Relevance
“…Moreover, at concentrations !10 lg/ml, Ag-NPs induced a significant decline in SSC proliferation by disrupting components of the Glial cell-derived neurotrophic factor (GDNF) signaling pathway, which is essential for SSC self-renewal in vivo and in vitro (Braydich-Stolle et al 2010). AgNPs was proven to be toxic for the cells involved in spermatogenesis, such as Leydig and Sertoli cells and SSCs and this toxicity was linked to a rapid ROS production and accumulation (Zhang et al 2015). High ROS levels in seminal plasma have been correlated with poor sperm morphology and is associated with the inhibition of sperm function and viability (Aziz et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, at concentrations !10 lg/ml, Ag-NPs induced a significant decline in SSC proliferation by disrupting components of the Glial cell-derived neurotrophic factor (GDNF) signaling pathway, which is essential for SSC self-renewal in vivo and in vitro (Braydich-Stolle et al 2010). AgNPs was proven to be toxic for the cells involved in spermatogenesis, such as Leydig and Sertoli cells and SSCs and this toxicity was linked to a rapid ROS production and accumulation (Zhang et al 2015). High ROS levels in seminal plasma have been correlated with poor sperm morphology and is associated with the inhibition of sperm function and viability (Aziz et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that AgNPs cause: DNA damage in germ cells, decrease sperm count and promote morphometric changes in seminiferous tubules (Dziendzikowska et al 2012;Gromadzka-Ostrowska et al 2012); decrease spermatogonia proliferation (Braydich-Stolle et al 2005, and increase germ cell apoptosis (Garcia et al 2014). In an elegant study, Zhang et al (2015) demonstrated that AgNPs induced massive cell death in TM3 (Leydig cell line) and TM4 (Sertoli cell line) cells, and inhibited proliferation and self-renewal of spermatogonial stem cells (SSCs). In this study AgNPs induced expression of autophagy-related genes and activated signaling molecules involved in apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs can cross the biological barriers to deposit in reproductive organs including testis, epididymis, ovary and uterus. Thus, AgNPs may damage germ cells and related cells, such as primary and secondary follicles, germline stem cells, Sertoli cells and Leydig cells 42 , 347 . Besides, AgNPs can also cause changes in sexual behavior by affecting the secretion of hormones within the reproductive organs and glands.…”
Section: Potential Toxicity Of Agnpsmentioning
confidence: 99%
“…Further studies confirmed that the reproductive toxicities of AgNPs are achieved by increasing inflammation, disrupting DNA structure, down-regulating gene expression, decreasing mitochondrial function, inducing ROS production and apoptosis. These toxicities of AgNPs to the reproductive system are size-, time- and dose-dependent 347 , 348 . Zhang et al 347 investigated the effects of AgNPs with different sizes (10 nm and 20 nm) on male somatic Leydig cells and Sertoli cells, and found that cell viability was inhibited by AgNPs in size- and concentration-dependent manners.…”
Section: Potential Toxicity Of Agnpsmentioning
confidence: 99%
“…Henceforth, the toxicity of AgNPs has been studied widely in many in vitro [4][5][6] and in vivo models [1,7,8]. Recent studies have demonstrated the adverse effects of AgNPs on the male reproductive tract, particularly spermatogenesis and the quality of sperm and male somatic cells and spermatogonial stem cells [9,10]. Early exposure to AgNPs has the potential to disrupt fetal and postnatal health in the embryo and abnormal development of the placenta [11].…”
Section: Introductionmentioning
confidence: 99%